Poverty Dynamics in Lithuania: Persistence, Transitions, Triggers - Navickė, Jekaterina (Lithuanian Journal of Statistics, 2015)
While Lithuania is among the countries with the highest at-risk-of-poverty rates in the European Union, povertyresearch has so far been dominated by cross-sectional poverty analysis. This paper is aimed at contributing to better understandingof poverty as a dynamic process in Lithuania by examining poverty risk persistence, transitions and triggers. Theanalysis is based on the longitudinal component of the Survey on Income and Living Conditions. The longitudinal at-risk-ofpovertyrate within the four-year panels is estimated to be at around a third of the Lithuanian population within a period of2005–2012. Poverty risk in Lithuania proved to be both widely spread and persistent. The major role of income events forpoverty risk entries and exits highlights the importance of activation into work, especially as concerns secondary householdearners and better income protection in Lithuania. While no robust evidence of poverty penalty was found for poverty exits,the incidence of poverty re-entries within the initial three-year period after poverty exit substantially exceeds poverty entryrates in the general population.